Recovery of pure lithium phosphate from sulfuric acid leaching solutions of spent LiFePO4 batteries by solvent extraction and chemical precipitation - Chen J.; Tran T. T.; Lee M. S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
With the increasing use of electric vehicles, the demand for lithium iron phosphate batteries (LiFePO4) has risen sharply. Therefore, the recycling of metals from these batteries at the end of their life is necessary. In this study, a hydrometallurgical process for the recovery of lithium phosphate from spent LiFePO4 batteries was developed. The effects of the parameters on the recovery process, consisting of leaching, solvent extraction, and precipitation were investigated. The addition of H2O2 to the H2SO4 solution was ineffective for the selective leaching of Li(I) over iron. The results showed that Li(I) and iron were completely dissolved by 1.5 mol/L H2SO4, 100 g/L pulp density at 25 °C for 60 min at 300 rpm. After oxidation of Fe(II) in the leaching solution by addition of H2O2, Fe(III) was completely separated from the solution by five steps of cross-flow extraction with 1.0 mol/L D2EHPA at room temperature. The loaded Fe(III) was successfully separated by four steps of cross-current stripping with 50% (v/v) aqua regia solution. Finally, most Li(I) was recovered by precipitation of lithium phosphate from the iron-free raffinate by maintaining the pH of the solution at 11 and the temperature at 95 °C for 30 min. The optimum conditions for the complete dissolution of LiFePO4 batteries by sulfuric acid solution and for the separation of iron and lithium ions from the leaching solutions were determined. A hydrometallurgical process was proposed for the recovery of pure lithium phosphate from spent LiFePO4 batteries.